Analysis of Factors associated with Nurses’ Compliance on the Implementation of Hand Hygiene - Yuanita Ananda; Netty Suharti; Mira Susanti (Elevate, 2018)
Background: Nosocomial infections are a major problem facing in the hospitals and can be spread by hand contact. Hand hygiene is one of the easier and more effective ways to prevent the nosocomial infection. Purpose: To determine kind of factors associated with nurses’ compliance in implementing hand hygiene at the inpatient installation in hospital. Method: It was an analytical descriptive study which collected the data through cross sectional design. The sample was 73 nurses taken by using proportional random sampling. Results: The result of the study showed that the nurses perceives high motivation (60,3%), high social support (56,2%), high knowledge (93,2%), complete facility (54,8%), good supervision (54,8% %), and nurse compliance (76.7%). There is no significant relationship between social supports, knowledge, facilities, and supervision factors with nurse compliance of hand hygiene implementation. However, there is a relationship between motivation factor and nurse compliance in implementing the hand hygiene. Conclusion: Therefore, it is recommended for the hospital to give rewards to the nurses who implement the hand hygiene properly and provide appropriate punishment for those who do not implement the hand hygiene properly